Diseaes of the Mind - Junqueira, Carmen (FCL-UNESP Laboratório Editorial, 2007)
This paper discusses the idea of disease in the native culture of the Kamaiurá, in which the idea of being healthy means necessarily being able of moving around, working – being alive means being healthy, free from something exterior that can cause harm to the body.